Directional regulation of the metabolic heterogeneity in anaerobic mixed culture to enhance fermentative hydrogen production by adaptive laboratory evolution. (29th June 2016) - Huang, Zhenxing; Yu, Jiangnan; Xiao, Xiaolan; Miao, Hengfeng; Ren, Hongyan; Zhao, Mingxing; Ruan, Wenquan
Abstract: In this study, an adaptive laboratory evolution strategy was originally developed to enhance fermentative hydrogen production by directionally regulating the metabolic heterogeneity in anaerobic mixed culture. The results indicated that the co-introduction of 4-methylpyrazole and oxamate could redistribute the metabolic flux to butyrate-type hydrogen fermentation. Subsequently, a synergistic evolutionary pressure, combining exogenous butyrate stress with 4-methylpyrazole and oxamate, was employed to evolve hydrogen-producing mixed culture with continuous fermentation system. The metabolic engineering strategy could directionally regulate the metabolic heterogeneity through efficiently shaping powerful butyrate-type hydrogen-producing community, by which evolved culture acquired a significantly improved hydrogen yield and productivity. Furthermore, compared with original culture, evolved culture possessed much higher activities of pyruvate-ferredoxin oxidoreductase and hydrogenase but a much lower ferredoxin-NAD + oxidoreductase activity, and these enzymatic evolutionary mechanisms were crucially important for the enhanced hydrogen fermentation. Highlights: 4-methylpyrazole and oxamate co-facilitated butyrate-type hydrogen fermentation. Hydrogen fermentation was significantly enhanced by an original ALE strategy. The activities of POR and hydrogenase was remarkably increased by the ALE strategy. The ALE strategy reduced the FNO activity of hydrogen-producing mixed culture.